Tindak Pidana secara Bersama Melakukan Tindakan Kekerasan yang Mengakibatkan Meninggal Dunia: Studi Kasus Putusan Mahkamah Agung Republik Indonesia Nomor 978 K/Pid/2020 - Kristanto, Antony (Rechtsnormen Jurnal Komunikasi dan Informasi Hukum, 2022)
Violence in society is actually not a new thing. Violence is often carried out together with one form of criminal act, as regulated in the Criminal Code (KUHP) for example theft with violence (Article 365 of the Criminal Code), persecution (Article 351 of the Criminal Code), rape (Article 285 of the Criminal Code), committing acts of violence against people or goods in public (Article 170 of the Criminal Code) and so on.